The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/15423050211073572
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Clinical Pastoral Education: How ACPE Educators Pivoted Amid the Pandemic

Abstract: Clinical Pastoral Education (CPE) programs faced extraordinary challenges during the COVID-19 pandemic. We examined how ACPE-certified educators responded to maintain program delivery. Survey results ( n = 210) suggested a substantial and abrupt increase in remote delivery for CPE instruction and supervised clinical practice, primarily driven by those previously fully in-person. Respondents reported abrupt changes impacted 1152 students. Participants rated their utilization and helpfulness of professional, org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Congruent with our previous quantitative findings (Szilagyi, Tartaglia et al, 2022), the qualitative data identified consultation from ACPE member Communities of Practice (CoP) as a key resource for educators. Many viewed this as such an important source of support that they planned to maintain newly formed connections with their CoP postpandemic.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Congruent with our previous quantitative findings (Szilagyi, Tartaglia et al, 2022), the qualitative data identified consultation from ACPE member Communities of Practice (CoP) as a key resource for educators. Many viewed this as such an important source of support that they planned to maintain newly formed connections with their CoP postpandemic.…”
Section: Discussionmentioning
confidence: 58%
“…The informed consent process was completed electronically at the beginning of the survey. Survey development and recruitment methods were further detailed in Szilagyi, Tartaglia et al (2022). The research protocol was reviewed and acknowledged as an exempt study by the Johns Hopkins Medicine Institutional Review Board (IRB00271136).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, participants reported positive student experiences while acknowledging the challenging aspects of the CPE course structure: balancing the demands of CPE and their work responsibilities, the course's pace, and in-person and online interactions. Parallel to participants' opinions on online and in-person CPE learning, CPE educators and students the USA reported certain benefits of online or hybrid modalities: ensuring access to CPE; not reducing the quality of learning; and being as effective as inperson CPE [42][43][44]. However, they desired more in-person interaction and found online learning not without limitations [42,43].…”
Section: Cpe For Chaplaincy Education In Englandmentioning
confidence: 94%
“…Parallel to participants' opinions on online and in-person CPE learning, CPE educators and students the USA reported certain benefits of online or hybrid modalities: ensuring access to CPE; not reducing the quality of learning; and being as effective as inperson CPE [42][43][44]. However, they desired more in-person interaction and found online learning not without limitations [42,43].…”
Section: Cpe For Chaplaincy Education In Englandmentioning
confidence: 94%